How contemporary international perspectives have consolidated a best-practice approach for identifying and developing sporting talent - Weissensteiner, J. R. (Routledge handbook of talent identification and development in sport, 2017)
The ability to effectively and consistently unearth future Olympic-, Paralympic- and Professional-level athletic talent through talent identification and development (TID) is the prized `holy grail` of any sporting nation. However, criticism in the literature persists regarding apparent conceptual, methodological and operational shortfalls in TID practice (Bergeron et al., 2015; Suppiah, Low, & Chia, 2015). The recently published International Olympic Committee`s (IOC) consensus statement on Youth Athlete Development (Bergeron et al., 2015) and aligned commentary highlight several limitations. These include, a lack of consensus regarding a viable overarching framework to inform TID `best practice`; a heavy emphasis on non-inclusive, uni-dimensional, low-predictive identification strategies in lieu of effective, individualised, long-term development; a lack of role clarity and expectations between stakeholders; inconsistency in aligned strategy, practice and support and questionable cost effectiveness and success (see also: Abbott & Collins, 2004; Abbott, Button, Pepping, & Collins, 2005; Ackerman, 2013; Buekers, Borry, & Rowe, 2015; Cobley, Schorer, & Baker, 2012; McCarthy & Collins, 2014; Malina, Rogol, Cumming, Coelho-e-Silva, & Figueiredo, 2015; Miller, Cronin, & Baker, 2015; Pinder, Renshaw, & Davids, 2013; Suppiah et al., 2015; Tucker & Collins, 2012; Vaeyens, Lenoir, Williams, & Philippaerts, 2008). Whilst boasting a rich history of successful programmes and international podium success, a recent review of pre-elite programmes in a number of Australian National Sporting Organisations (Weissensteiner & Medlicott, 2015) also revealed a number of system- and sport-specific level gaps in current TID initiatives. The review outlined a need for ongoing education of all key stakeholders, including coaches and high performance managers regarding evidence-informed best practice approaches for maximising TID; better clarity regarding the coordination, communication and consistency ofTID strategies; and further consolidation of talent transfer approaches. Additionally it highlighted the criticality of ongoing athlete monitoring to inform and enhance the individualised, interdisciplinary case management of athletes. Cognisant of these limitations, the need for a theoretical yet practicable overarching framework to inform effective TID strategy and `best practice` is critical. In this chapter, contemporary international perspectives and advances in approaches to TID will be showcased. These are then consolidated within a viable, evidence-based, practicable framework and national strategy that is currendy guiding TID practice within the Australian sporting system.